Favoring the Retreat of Secularization. Corporative Catholicism and State in Peru, 1920-1945 - Armas Asín, Fernando (Jahrbuch für Geschichte Lateinamerikas, 2025)
This study outlines, for the period between 1920 and 1945 -marked by the global economic crisis, World War, authoritarianism or the increasing social control of the State-, how the corporatist vision existing within the hierarchy of the Peruvian Catholic Church and the presence of authoritarian governments allowed closer collaboration between the Church and the State in several fields, as opposed to their immediate past. This collaboration achieved the elimination or limitation of some existing secularizing norms and practices. The specific aspects of these changes are reviewed and their consequences are discussed. This study may help to provide a better understanding of the relationship between authoritarianism and religion in Latin America.
Keywords: Latin America; Clergy; State; Catholic Church; Church-State Relations.